S58 Fev1 and feno as predictors of asthma outcomes in children? an individual patient data analysis using data from six feno trials. (15th November 2017) - Fielding, S; Pijnenburg, M; Jongste, J de; Pike, K; Roberts, G; Petsky, H; Chang, A; Fritsch, M; Frischer, T; Szefler, S; Gergen, P; Vermeulen, F; et al.
Abstract : Introduction: Some guidelines advocate using FEV1 and/or fractional exhaled nitric oxide (FeNO) in the management of childhood asthma, but evidence supporting these recommendations is generally unsupportive. Our hypothesis was that reduced FEV1 and/or elevated FeNO measurements were associated with increased risk of future asthma attacks and loss of asthma control. Methods: Data were obtained from six trials where FeNO was used to guide asthma treatment. Baseline% FEV1 and FeNO were linked to exacerbation and loss of control between baseline and three months. Change in% FEV1 and% change in FeNO between baseline and 3 months were also linked to exacerbation and loss of control between three and six months after baseline. A one-stage individual patient data meta-analysis was conducted using a random effect for study. Baseline confounders included in the model were age, sex, LABA, LTRA, ICS dose, trial arm, control and FeNO or FEV1 as appropriate. Results: Data were available in 1049 children (58% male, mean age 12.7 years) from six trials. Each unit reduction in baseline% FEV1 was associated with increased risk for future exacerbation (OR 1.02 [1.00, 1.03] n=935, p=0.034) and with increased risk for loss of control (1.01 [1.00, 1.02], n=940, p=0.026) after three months. Similar associations were present between change in%FEV1 and outcomes after six months. Baseline FeNO was not related to asthma outcomes but each 10% increase in FeNO between baseline and three months was associated with increased risk for loss of asthma control by six months (OR 1.02 [1.01, 1.03], n=725, p=0.009) but not with asthma exacerbation. Falling% FEV1 and rising% FeNO between baseline and three months were independently associated with loss of control at six months. Conclusions: Baseline% FEV1 is rather weakly associated with future asthma outcomes, and change in%FEV1 between visits does not strengthen this association. In contrast, baseline FeNO is not related to future outcomes but% change in FeNO has some precision for future asthma control. The utility of%FEV1 and FeNO in childhood asthma management needs to be rigorously evaluated in a clinical trial.